2006
DOI: 10.2116/analsci.22.1125
|View full text |Cite
|
Sign up to set email alerts
|

Borate Cross-Linked/Total Rhamnogalacturonan II Ratio in Cell Walls for the Biochemical Diagnosis of Boron Deficiency in Hydroponically Grown Pumpkin

Abstract: Boron (B) is an essential trace element for vascular plants, 1,2 and B deficiency inhibits the growth of root and shoot tips. 3 The B deficiency in field crops has been reported for various species and in many countries. 4 B deficiency is diagnosed by plant symptoms and by soil and plant analysis for good crop management. 5In plant analysis for mineral nutrition diagnosis, 6,7 the total mineral content of leaves is frequently determined to compare with the critical content. Based on the role and behavior of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…In a study of pumpkin roots exposed to low-B conditions, RG-II-B dimer formation decreased along with the root dry weight (Matsunaga and Ishii, 2006). In pumpkin roots subjected to B-depleted conditions (no addition of B), the fraction of RG-II forming the borate complex was about 55% (Matsunaga and Ishii, 2006). Under these conditions, the pumpkin root dry weight was about 50% lower than under the B-sufficient conditions.…”
Section: Table I Rg-ii-b Dimer Formation and B Concentration Of Arabmentioning
confidence: 95%
See 3 more Smart Citations
“…In a study of pumpkin roots exposed to low-B conditions, RG-II-B dimer formation decreased along with the root dry weight (Matsunaga and Ishii, 2006). In pumpkin roots subjected to B-depleted conditions (no addition of B), the fraction of RG-II forming the borate complex was about 55% (Matsunaga and Ishii, 2006). Under these conditions, the pumpkin root dry weight was about 50% lower than under the B-sufficient conditions.…”
Section: Table I Rg-ii-b Dimer Formation and B Concentration Of Arabmentioning
confidence: 95%
“…B is distributed primarily to cell walls prior to its accumulation in the soluble fraction of Arabidopsis roots under low-B conditions (Noguchi et al, 2000). The RG-II-B complex is known to occur in radish roots (Kobayashi et al, 1996) and pumpkin (Cucurbita maxima) roots (Matsunaga and Ishii, 2006). In a study of pumpkin roots exposed to low-B conditions, RG-II-B dimer formation decreased along with the root dry weight (Matsunaga and Ishii, 2006).…”
Section: Table I Rg-ii-b Dimer Formation and B Concentration Of Arabmentioning
confidence: 99%
See 2 more Smart Citations
“…Matsunaga and Ishii (2006) reported a method for assessing B deficiency by analyzing the formation of cross-links of the pectin RG-II domain that function as B carriers. They also showed that 90-100% of dRG-II-B corresponds to sufficient B, 50-80% corresponds to underlying deficiency, and less than 40% corresponds to B depletion and disturbances in growth.…”
Section: Discussionmentioning
confidence: 99%